Analisis Kelayakan Ekonomi dan Risiko Pendapatan Usaha Peternakan Itik Petelur di Desa Kebonsari Kecamatan Candi Kabupaten Sidoarjo - Nada, Irma Qotrun; Soedarto, Teguh; Tondang, Ika Sari (Universitas Batanghari Jambi, 2024)
The research aims to 1) Identify the state of the laying duck farm business 2) Analyze the economic feasibility of laying duck farming 3) Analyze the income risk of laying duck farming. The research location was selected using a purposive method. The research was conducted using quantitative methods with a descriptive approach. Sample determination was carried out by the saturated sampling method with a population of 16 laying duck farmers, and the entire population was sampled. The results of the research that has been carried out with an average livestock land area of 1271.9 m2 get the results of economic feasibility with a value of R / C Ratio of 1.28, B / C Ratio of 0.28, BEP Production 16,341, and BEP Price of Rp 1,963. The research conducted states that the business is said to be economically feasible and has a low-risk value and has value for further development.